Pengaturan Pemberian Kompensasi Bagi Pekerja dalam Hubungan Kerja Berdasarkan Perjanjian Kerja Waktu Tertentu (PKWT) - Hidayati, Nuri; Lutfianidha, Redyana; Dewi, Rinda Atika (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Sekolah Tinggi Islam Blambangan (STIB) Banyuwangi, 2024)
The purpose of writing this article is that workers who are in an employment relationship based on a Specific Time Work Agreement (PKWT) have the right to receive compensation money in accordance with statutory provisions. The research method used is juridical-normative, namely legal research by examining statutory regulations and literature study (secondary material). PKWT is an agreement between workers and employers to enter into an employment relationship for a certain period of time at the company's choice when recruiting workers. The motive behind this choice is the entrepreneur's desire to achieve large profits with small capital. However, since the implementation of the PKWT provisions in the Government Regulation of the Republic of Indonesia Number 35 of 2021 concerning Specific Time Work Agreements (PKWT), Outsourcing, Working Time and Rest Time, and Termination of Employment Relations has become different. That PKWT system workers whose contract period has ended are entitled to receive compensation money from the Company as regulated in Article 15. If the compensation money is not given then the company (entrepreneur) will receive administrative sanctions in the form of a written warning, restrictions on business activities, partial or complete temporary suspension production equipment, and freezing business activities in accordance with the provisions of Article 61 of the Republic of Indonesia Government Regulation Number 35 of 2021 concerning Specific Time Work Agreements (PKWT), Outsourcing, Working Time and Rest Time, and Termination of Employment Relations.